ANALISIS KINERJA ENVIRONMENTAL, SOCIAL, AND GOVERNANCE (ESG) TERHADAP EFISIENSI INVESTASI PERUSAHAAN DENGAN JANGKA WAKTU UTANG DAN KENDALA PENDANAAN SEBAGAI VARIABEL MODERASI (Studi Empiris pada Perusahaan Energi, Infrastruktur, Real Estate, dan Pertambangan Tahun 2018-2024) - An Nisaa Itsar Kusuma Maharani; Agus Purwanto (Diponegoro Journal of Accounting, 2026)
This study aims to analyze the effect of Environmental, Social, and Governance (ESG) performance on corporate investment efficiency, with debt maturity and financing constraints as moderating variables. This study employs a quantitative approach using secondary data obtained from annual reports, sustainability reports, Bloomberg, and the Indonesia Stock Exchange (IDX). The population consists of companies in the energy, infrastructure, real estate, and mining sectors listed on the Indonesia Stock Exchange during the 2018–2024 period. The sample was selected using a purposive sampling method, resulting in 18 companies with a total of 125 observations. Data were analyzed using panel data regression with the Moderated Regression Analysis (MRA) approach.The results indicate that ESG performance has a significant effect on corporate investment efficiency. In addition, debt maturity is able to moderate the relationship between ESG and corporate investment efficiency, whereas financing constraints are unable to moderate the relationship between ESG and corporate investment efficiency. These findings suggest that ESG implementation in energy, infrastructure, real estate, and mining companies in Indonesia has not yet fully improved the quality of corporate investment decisions. Furthermore, the company's financing conditions have not strengthened the relationship between ESG implementation and investment efficiency.This study contributes to the development of the literature on ESG and investment efficiency, particularly in capital-intensive industries within emerging markets. The findings are also expected to provide insights for companies and investors regarding the importance of ESG implementation and financing management in supporting corporate sustainability.